The implication of forward ijarah in Malaysia : prospects and challenges - Amer, Khaled M.M (Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2014)
One of the most successful of the Islamic lunovative Financial Product in recent years in the Middle East is forward ijarah. This concept is considered as one of the popular contracts that has been applied in various applications in the practice. Due to the success of this contract_ the Islamic Financial Institutions in Malaysia has established the application of forward iilirah to their customers. The main product that has been offered is house tlnancing either as a standalone product or as a supporting contact that is combined with others. This research paper therefore attempts to discuss the concept of t(m\ard ij1irah and its implications. Specifically this study presents its legality, its various types (i.e. lease. usufructs. and human usufructs), its conditions and rules of the practice of forward ijarah according to Islamic Law. Moreover. the paper reviewed the opinions of dtfferent scholars regarding the permissibility of forward ijtirah and also the comparison of forward ijtirah to other modes of fmance. ltalso discusses the governing law on forward ijtirah. Besides. it also discusses a sample of legal documentation of forward ijarah contract. Furthermore. the paper discusses also some of the important issues surrounding the implementation of forward ijtirah. Finally, this paper summarized the prospects and challenges of implementing forward ijtirahin Islamic Financial Institutions nowadays. It also gives recommendation to move forward with forward iitirah in the Malavstan Islamic Financial industry. Keywords: Forward !jarah. Prospects. Challenges, Malaysia